Question
upstudy study bank question image url

Let \( Z=x^{2} \sin \left(3 x+y^{3}\right) \) (a) Evaluate \( \frac{\partial z}{\partial x} \) at \( \left({ }^{2} / 3,0\right) \) (b) Evaluate \( Z_{y} \) at \( (1,1) \)

Ask by Dawson Watkins. in Nigeria
Jan 11,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**Part (a):** At \( \left(\frac{2}{3}, 0\right) \), the partial derivative \( \frac{\partial Z}{\partial x} \) is \( \frac{4}{3} (\sin(2) + \cos(2)) \). **Part (b):** At \( (1, 1) \), the partial derivative \( Z_{y} \) is \( 3 \cos(4) \).

Solution

Let's evaluate the partial derivatives of the function \( Z = x^{2} \sin(3x + y^{3}) \) as requested. ### Part (a): Evaluate \( \frac{\partial Z}{\partial x} \) at \( \left(\frac{2}{3}, 0\right) \) **Step 1: Compute the Partial Derivative with Respect to \( x \)** Given: \[ Z = x^{2} \sin(3x + y^{3}) \] Using the product rule for differentiation: \[ \frac{\partial Z}{\partial x} = \frac{d}{dx}(x^{2}) \cdot \sin(3x + y^{3}) + x^{2} \cdot \frac{d}{dx}[\sin(3x + y^{3})] \] Compute each part: \[ \frac{d}{dx}(x^{2}) = 2x \] \[ \frac{d}{dx}[\sin(3x + y^{3})] = \cos(3x + y^{3}) \cdot \frac{d}{dx}(3x + y^{3}) = 3 \cos(3x + y^{3}) \] Thus: \[ \frac{\partial Z}{\partial x} = 2x \sin(3x + y^{3}) + 3x^{2} \cos(3x + y^{3}) \] **Step 2: Evaluate at \( \left(\frac{2}{3}, 0\right) \)** Plugging in \( x = \frac{2}{3} \) and \( y = 0 \): \[ \frac{\partial Z}{\partial x}\Bigg|_{\left(\frac{2}{3},0\right)} = 2\left(\frac{2}{3}\right) \sin\left(3 \cdot \frac{2}{3} + 0^{3}\right) + 3\left(\frac{2}{3}\right)^{2} \cos\left(3 \cdot \frac{2}{3} + 0^{3}\right) \] \[ = \frac{4}{3} \sin(2) + \frac{12}{9} \cos(2) \] \[ = \frac{4}{3} \sin(2) + \frac{4}{3} \cos(2) \] \[ = \frac{4}{3} (\sin(2) + \cos(2)) \] **Final Answer for Part (a):** \[ \frac{\partial Z}{\partial x}\Bigg|_{\left(\frac{2}{3},0\right)} = \frac{4}{3} \left( \sin(2) + \cos(2) \right) \] --- ### Part (b): Evaluate \( Z_{y} \) at \( (1, 1) \) **Step 1: Compute the Partial Derivative with Respect to \( y \)** Given: \[ Z = x^{2} \sin(3x + y^{3}) \] Differentiate with respect to \( y \): \[ \frac{\partial Z}{\partial y} = x^{2} \cdot \frac{d}{dy}[\sin(3x + y^{3})] = x^{2} \cdot \cos(3x + y^{3}) \cdot \frac{d}{dy}(3x + y^{3}) \] \[ = x^{2} \cdot \cos(3x + y^{3}) \cdot 3y^{2} \] \[ = 3x^{2} y^{2} \cos(3x + y^{3}) \] **Step 2: Evaluate at \( (1, 1) \)** Plugging in \( x = 1 \) and \( y = 1 \): \[ \frac{\partial Z}{\partial y}\Bigg|_{(1,1)} = 3(1)^{2} (1)^{2} \cos(3 \cdot 1 + 1^{3}) = 3 \cos(4) \] **Final Answer for Part (b):** \[ Z_{y}\Big|_{(1,1)} = 3 \cos(4) \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find \( Z = x^{2} \sin(3x + y^{3}) \), we will compute the partial derivatives and then evaluate them at the specified points. (a) To find \( \frac{\partial Z}{\partial x} \), we use the product and chain rules. \[ \frac{\partial Z}{\partial x} = \frac{\partial}{\partial x}(x^{2}) \sin(3x + y^{3}) + x^{2} \frac{\partial}{\partial x}(\sin(3x + y^{3})) \] Calculating the first term: \[ \frac{\partial}{\partial x}(x^{2}) = 2x \quad \Rightarrow \quad 2x \sin(3x + y^{3}) \] Calculating the second term using the chain rule: \[ \frac{\partial}{\partial x}(\sin(3x + y^{3})) = \cos(3x + y^{3}) \cdot \frac{\partial}{\partial x}(3x + y^{3}) = 3\cos(3x + y^{3}) \] So, the second term becomes: \[ x^{2} \cdot 3\cos(3x + y^{3}) = 3x^{2} \cos(3x + y^{3}) \] Combining both parts, we have: \[ \frac{\partial Z}{\partial x} = 2x \sin(3x + y^{3}) + 3x^{2} \cos(3x + y^{3}) \] Now, evaluating at the point \(\left(\frac{2}{3}, 0\right)\): \[ \frac{\partial Z}{\partial x}\bigg|_{\left(\frac{2}{3}, 0\right)} = 2\left(\frac{2}{3}\right) \sin\left(3\left(\frac{2}{3}\right) + 0^{3}\right) + 3\left(\frac{2}{3}\right)^{2} \cos\left(3\left(\frac{2}{3}\right) + 0^{3}\right) \] \[ = \frac{4}{3} \sin(2) + 3 \cdot \frac{4}{9} \cos(2) = \frac{4}{3} \sin(2) + \frac{4}{3} \cos(2) = \frac{4}{3}(\sin(2) + \cos(2)) \] Thus, the final answer for part (a) is: \[ \frac{\partial Z}{\partial x}\bigg|_{\left(\frac{2}{3}, 0\right)} = \frac{4}{3}(\sin(2) + \cos(2)) \] (b) To find \( \frac{\partial Z}{\partial y} \) (denoted \( Z_{y} \)), we apply the chain rule: \[ \frac{\partial Z}{\partial y} = x^{2} \cos(3x + y^{3}) \cdot \frac{\partial}{\partial y}(3x + y^{3}) = x^{2} \cos(3x + y^{3}) \cdot 3y^{2} \] Thus, \[ Z_{y} = 3yx^{2} \cos(3x + y^{3}) \] Now, evaluating at the point \( (1, 1) \): \[ Z_{y}(1, 1) = 3(1)(1)^{2} \cos(3(1) + 1^{3}) = 3 \cos(4) \] Therefore, the final answer for part (b) is: \[ Z_{y}(1, 1) = 3 \cos(4) \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy